An ICT-based fluorescence enhancement probe for detection of Sn2+ in cancer cells. Issue 62 (13th October 2020) - Meng, Xiangying; You, Lai; Li, Siyuan; Sun, Qi; Luo, Xiaogang; He, Haifeng; Wang, Jinglan; Zhao, Feng
Abstract : Development of a novel fluorescence enhancement probe for detection of Sn 2+ in organisms, with high selectivity and sensitivity, is of great interest but remains a great challenge. Abstract : Development of a novel fluorescence enhancement probe for detection of Sn 2+ in organisms, with high selectivity and sensitivity, is of great interest but remains a great challenge. Herein, an ICT-based fluorescence probe TPPB was rationally developed to act as an 'enhancement' luminescent and "naked-eye" indicator for Sn 2+ detection. Importantly, spectroscopic studies indicated that TPPB was a fluorescence enhancement sensor for Sn 2+ with rapid response, low detection limit (0.116 μM) and excellent binding constant (1.6 × 10 4 M −1 ). The mechanism of TPPB response to Sn 2+ was further proved by 1 H NMR titration, and enhancement calculations. Furthermore, TPPB is applied as a fluorescence probe for imaging in Hela cells, indicated that it can be potentially applied for Sn 2+ sensing in biological fields.